2021
DOI: 10.1007/s00737-021-01157-w
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated risk for obsessive–compulsive symptoms in women pregnant during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has led to a public mental health crisis with many people experiencing new or worsening anxiety. Fear of contagion and the lack of predictability/control in daily life increased the risk for problems such as obsessive-compulsive disorder (OCD) in the general population. Pregnant women may be particularly vulnerable to such pandemic-related stressors yet the prevalence of OC symptoms in this population during the pandemic remains unknown. We examined the prevalence of OC symptoms in a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…Various studies evaluated the prevalence of psychopathological symptoms during COVID-19 pandemic in pregnant women: recent systematic reviews and meta-analyses observed the prevalence of depressive symptoms between 25 and 30% and the one of anxiety symptoms between 34 and 42% ( 13 , 14 ). Concerning OCD symptoms, some studies assessed its prevalence in pregnant women during COVID-19 pandemic between 7.12 ( 49 ) and 10.3% ( 50 ), in line with our study.…”
Section: Discussionsupporting
confidence: 85%
“…Various studies evaluated the prevalence of psychopathological symptoms during COVID-19 pandemic in pregnant women: recent systematic reviews and meta-analyses observed the prevalence of depressive symptoms between 25 and 30% and the one of anxiety symptoms between 34 and 42% ( 13 , 14 ). Concerning OCD symptoms, some studies assessed its prevalence in pregnant women during COVID-19 pandemic between 7.12 ( 49 ) and 10.3% ( 50 ), in line with our study.…”
Section: Discussionsupporting
confidence: 85%
“…The COVID-19 pandemic process has led to a mental health crisis for the public, during which many people have been anxious. In this process, the fear of infection and the lack of control in daily life increased the risk of problems such as obsessive-compulsive disorder not only in pregnant women but also in the general population (Mahaffey et al, 2022). Therefore, those who exhibit obsessive-compulsive symptoms can be said to experience these symptoms as a result of their anxiety about their health (Taylor et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this period, the fear of infection and lack of control in daily life have increased the risk of problems such as obsessive-compulsive disorder, not only in pregnant women but also in the general population. 32 In other words, it is not surprising that we found a positive relationship between anxiety and obsession levels and anxiety and fear of childbirth. There are studies showing that the fear of childbirth is higher in complicated pregnancies.…”
Section: Discussionmentioning
confidence: 73%